2018
DOI: 10.1590/1678-5150-pvb-5686
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of skin tumors in dogs in Salvador, Bahia state, Brazil (2007-2016)

Abstract: This study aimed to establish the incidence of skin tumors (cutaneous proliferative lesions of neoplastic or non-neoplastic nature) in dogs diagnosed by histopathological evaluation at the Veterinary Pathology Laboratory (LPV) of the Federal University of Bahia (UFBA) in a 10-year (2007-2016) historical series. Of the 1945 histopathological diagnoses made in this period, 503 were skin biopsies, and 617 dermatological problems (87 dogs, 17.3%, presented more than one positive diagnosis) were found. Of the 617 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
4
8
2
1
Order By: Relevance
“…Skin tissue samples comprised of almost 50% of all canine samples during the period under evaluation. Previous studies have shown that skin lesions constitute the highest number of pathological diagnoses in dogs (Meirelles et al 2010, Silva et al 2011, Graf et al 2018, Machado et al 2018. Neoplastic lesions can range from 49.9% to 75.8% of all skin lesions (Souza et al 2006, Machado et al 2018), a finding similar to the results found in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Skin tissue samples comprised of almost 50% of all canine samples during the period under evaluation. Previous studies have shown that skin lesions constitute the highest number of pathological diagnoses in dogs (Meirelles et al 2010, Silva et al 2011, Graf et al 2018, Machado et al 2018. Neoplastic lesions can range from 49.9% to 75.8% of all skin lesions (Souza et al 2006, Machado et al 2018), a finding similar to the results found in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…About 9.8% of the dogs in this study had more than one skin neoplasms, irrespective of whether they were of the same histological type. Similar results were found in other studies, adding the chance of occurrence of non-neoplastic tumors (Souza et al 2006, Machado et al 2018. These data highlight the importance of the clinical veterinarians and the veterinary surgeons sending samples of all skin tumors for histological analysis, despite the possibility that they are of the same histological type.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recent studies have reviewed 11,740 canine skin tumors in Switzerland (Graf et al, 2018); 2,553 cases in South Africa (Tompkins et al, 2019); and 546 cases in Brazil (Machado et al, 2018). In these reports, tumors with most incidence were mast cell tumor and lipoma in common, and it was in accord with a previous report from Korea (Pakhrin et al, 2007).…”
Section: Introductionsupporting
confidence: 73%
“…Although there were some differences between the findings in this study and those of previous reports, tumors showing the highest frequency were generally similar between studies (Pakhrin et al, 2007;Graf et al, 2018;Machado et al, 2018). This may reflect that specific cell populations are particularly vulnerable to tumorigenic stimulation.…”
Section: Discussioncontrasting
confidence: 51%